Influence of Forest Management Regimes and Soil Depth on Some Selected Soil Properties - Neupane, Asmit; Dhakal, Anisha; Kahtiwada, Praju; Acharya, Bashundhara; Dahal, Ashma (FORESTRY: Journal of Institute of Forestry, Nepal, 2024)
Forest management activities and soil depth can significantly impact soil characteristics and carbon sequestration. This study assessed variations in soil pH, Soil Organic Carbon (SOC) %, and Available Nitrogen across different community-based forest management (CBFM) regimes and soil depths in the Mahottari district of Nepal. The results indicated significant differences among management regimes for all three soil parameters (p < 0.05). Soil pH ranged from 5.6 ± 0.2 in Leasehold Forest (LF) to 6.4 ± 0.1 in Religious Forest (RF), showing a decreasing trend from LF to Community Forest (CF), Collaborative Forest Management (CBM), and RF, with no consistent depth-related trend (p = 0.12 for depth interaction). SOC % varied significantly, declining from 2.6 ± 0.3% in CF to 1.8 ± 0.2% in RF and 1.5 ± 0.1% in LF (p < 0.001), with a consistent decrease across depths. Similarly, Available Nitrogen showed a linear decline across regimes, from 230 ± 15 mg/kg in CF to 140 ± 10 mg/kg in LF (p < 0.01), with depth also influencing nitrogen availability (p < 0.05). These findings suggest that while soil pH remains relatively stable with depth, SOC % and Available Nitrogen are highly sensitive to both management regime and soil depth. The study recommends targeted forest management practices to enhance soil organic carbon stocks and improve soil fertility across CBFM regimes.